Interaction Design on Basic Hand Movement Training Game in Taekwondo Using User-Centered Design - Ramdani, Rahmat Muhamad; Yuniarti, Rezki; Komarudin, Agus (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
This research will develop an interaction design for basic hand movement games in taekwondo with the hope that it can become an alternative physical exercise for hand stretching. UCD is one of the methods in interaction design that focuses on the user. By designing interactions in hand movement training games using the UCD method and present technology, it is hoped that this can be a stretch in the dense student activities. The results of the interaction design evaluation using UCD obtained an average of 90.24% for the 6th heuristic based on ten evaluation heuristics. Combining the UCD method at the design stage and utilizing present technology is an innovation in designing easy-to-use game-based interaction designs. The study results show that the UCD method for interaction design is suitable for use in the game design process.